Moral dilemmas and slow codes. - Crutchfield, Parker (Bioethics, 2025)
Slow codes—insincere attempts at resuscitation—are widely regarded in medicine and medical ethics as morally impermissible. My goal here is to enrich this special issue on the slow code with an argument for the permissibility of slow codes that is rooted in moral psychology. Specifically, if we take seriously the results from moral psychology, the slow code is not only permissible, it is often the best option. The context of the decision about whether to perform a slow code is analogous to thoroughly investigated moral dilemmas such as the trolley problem. In particular, when the trolley problem is framed as a trilemma, it becomes clear that the decisional context of the slow code is analogous to the famous moral dilemma. Since in the trolley problem the choice analogous to the slow code is the best choice, the slow code may be the best choice when facing patient or family requests for futile CPR. In establishing this claim, I address a range of objections to the slow code. I conclude with an empirically supported explanation of the conventional wisdom. Resistance to the slow code doesn't sprout from the act's moral properties, but from moral judgments influenced by other factors, such as emotion, physical distance, and personal force.